The Effect of Implementation of the Government’s Internal Control System on Fraud Prevention on the Management of Social Assistance Funds in Jambi City - Nabila Azzahra Abas; Enggar Diah Puspa Arum; Rahayu (Indonesian Journal of Economic & Management Sciences, 2023)
This study aims to determine the effect of implementing the government’s internal control system on fraud prevention on the management of social assistance funds in Jambi City. This study is a quantitative research using primary data obtained from questionnaires. The population of this study were all employees in the Inspectorate of Jambi City, namely as many as 56 employees. The sampling technique used purposive sampling with the criteria of employees who are included in the organizational structure and auditors, based on these criteria a total of 34 samples were obtained. The data analysis technique used is SEM-PLS using SmartPLS 3.0. The results showed that only monitoring has an effect on fraud prevention. While control environment, risk assessment, control activities, information and communication had no effect on fraud prevention